Temperature sensitivity of permafrost carbon release mediated by mineral and microbial properties - Qin, Shuqi; Kou, Dan; Mao, Chao; Chen, Yongliang; Chen, Leiyi; Yang, Yuanhe (Science Advances, 2021)
Temperature sensitivity (Q(10)) of permafrost carbon (C) release upon thaw is a vital parameter for projecting permafrost C dynamics under climate warming. However, it remains unclear how mineral protection interacts with microbial properties and intrinsic recalcitrance to affect permafrost C fate. Here, we sampled permafrost soils across a 1000-km transect on the Tibetan Plateau and conducted two laboratory incubations over 400- and 28-day durations to explore patterns and drivers of permafrost C release and its temperature response after thaw. We find that mineral protection and microbial properties are two types of crucial predictors of permafrost C dynamics upon thaw. Both high C release and Q(10) are associated with weak organo-mineral associations but high microbial abundances and activities, whereas high microbial diversity corresponds to low Q(10). The attenuating effects of mineral protection and the dual roles of microbial properties would make the permafrost C-climate feedback more complex than previously thought.